Porównanie kultury strategicznej Stanów Zjednoczonych i Chińskiej Republiki Ludowej - Wójtowicz, Tomasz (Polityka i Społeczeństwo, 2020)
Strategic culture in the theory of international relations is now one of the most important concepts explaining the rules of military behaviour by individual states. In contrast to realism and idealism, its focuses on the influence of internal factors on foreign policy, such as historical experience, national identity, morals in society, and perception of diplomacy by political elites. It therefore allows us to respond to many questions that researchers are not able to answer based solely on the theory of political realism ‒ the perception of national security threats by governments, the national way of war, the socially-acceptable level of victims, the attitude of armed forces to the use of new technologies, or trust to allies. The purpose of this article is to compare the strategic culture of the United States and the People’s Republic of China ‒ states with significantly different strategic cultures, historical experience, national identity and methods of warfare. The content of this article may be useful to any person interested in Sino-American relations, political rivalry in the Western Pacific and a possible future war between these powers.